Physicochemical Properties and Antioxidant Activity of Essential Oil from Fresh, Wilted, and Dried Leaves of Holy Basil (Ocimum tenuiflorum L.) Planted in Yogyakarta - Hetty Sri Mulyati; Rini Yanti; Supriyadi Supriyadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2023)
This study aimed to determine the effect of drying and distillation time on the physicochemical properties and antioxidant activity of essential oil from holy basil (Ocimum tenuiflorum) leaves. The leaves were subjected to different drying treatments to obtain fresh, wilted, and dried samples. The microstructure tissue of the various treatment samples was observed using a Scanning Electron Microscope (SEM). Subsequently, essential oil was extracted using the water and steam distillation method for 3, 4, 5, and 6 hours. The distilled essential oil was tested for its physicochemical properties (specific gravity, refractive index, acid number, and solubility in alcohol), and the compound composition evaluation was carried out using Gas Chromatography-Mass Spectrometry (GCMS). The antioxidant activity was then determined using the DPPH (1,1-diphenyl- 2-picrylhydrazyl) method. The results showed that the fresh leaves distillation for 5 hours produced the highest oil yield of 0.62%. The physicochemical properties were 0.986 g/ml specific gravity, 1.339 refractive index, 1.8 mg KOH/g acid value, and 1:1 solubility in alcohol. The major component of the product was methyl isoeugenol (20.50%), bete-element (15.07%), eugenol (13.59%), germacrene D (14.2%), and ylangene (7.46). The results of the antioxidant activity test showed that the essential oil of holy basil could be included in the powerful natural antioxidant category, with an IC50 value of 7,895 μg/mL.